The Effect of Financial Compensation, Competency, Leadership Style on the Work Satisfaction - Kamaluddin, Apiaty; Hatidja, St.; Marmin, Hidayat (Manunggal Halim Jaya, 2022)
The aims of this study are 1) to analyze the influence of financial compensation, competence, competency, leadership style on the work satisfaction; and 2) to analyze which variables are dominantly affect on dependend varible. The data used are primary data and secondary data. The population in this study were all employees of the Regional Secretariat of the City of Parepare, amounting to 105 people. The sample was determined using the Slovin formula to obtain as many as 83 respondents. Data were collected through observation, questionnaires, and documentation. The data analysis method used descriptive statistical analysis and multiple linear regression using the SPSS program. The result of this study states all hypothesis positevely affect on depende variables.